Prokrastinasi Akademik Mahasiswa Tingkat Akhir: Studi tentang Hubungan Locus of Control dan Strategi Coping: Indonesia - Enindari, Woro Nauraningrum; Nurmala , Sukma (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2023)
The purpose of this study was to determine the relationship between locus of control and coping strategies with academic procrastination of final year students. This study used a correlational quantitative approach involving 138 participants. The criteria for respondents in this study were active final year students (semester 7 and above) at universities in Indonesia and were working on a thesis. There are 3 measuring instruments used, namely The Multidimensional Locus of Control IPC Scale (2011), Academic Coping Strategy Scale (2017), and Academic Procrastination Scale (2020). The results of this study indicate a positive relationship (the direction of the relationship is directly proportional) between locus of control and academic procrastination and a negative relationship (the direction of the relationship is inversely proportional) between coping strategies and academic procrastination. Keywords: Locus of Control, Final Year Students, Academic Procrastination, Coping Strategies.